Determinantes del acceso y uso de la inclusión financiera en el área urbana en países de la Comunidad Andina. Periodo 2005-2018. - Córdova Galarreta, Allison (2021)
Financial inclusion is important as it has an impact on poverty reduction, inequality reduction and economic growth. The objective of this research is to find the determinants of access and use of financial inclusion in Peru, Colombia, Ecuador and Bolivia. It is the main hypothesis that the models have explain the access and use of financial inclusion in the urban area in the countries of the Andean Community in the period 2005-2018; The dependent variables are access to Deposits / GDP, Credits / GDP and the number of ATMs in use. Regarding the non-experimental design, the research is as far as its scope is explanatory and econometric. For the use models, it is true that the variables of legality index, credit information index, GDP per capita, private credit registries, education spending and population density have a positive relationship to increase financial inclusion, with the credit information index being, GDP per capita and spending on education the variables that had the greatest impact. On the other hand, in the access model it was found that the variables GDP per capita, private credit records, credit information index have a positive relationship and the variable population density a negative relationship; the variables with the greatest impact are the credit information index and GDP per capita. It can be concluded that there is an excess supply in areas already financially penetrated and there are no incentives to open service points in isolated areas due to the high costs that these imply. Further research on the determinants for financial inclusion and market research on underserved populations is recommended in order to propose products that fit their needs.